Effectiveness of the Online Marriage Management Information System (SIMKAH) at the Religious Affairs Office (KUA) in Sukorambi District, Jember Regency - Lilis Beta Utami; Abdul Hadi; Abdul Latib (Takaza Innovatix Labs Ltd., 2026)
The development of digitalization of public services has encouraged the Office of Religious Affairs (KUA) to implement an online-based Marriage Management Information System (SIMKAH) to improve the quality of marriage registration administration. This study aims to analyze the effectiveness of the online-based SIMKAH implementation at the Office of Religious Affairs in Sukorambi District, Jember Regency. The study used a qualitative approach with descriptive methods. The study population included all parties involved in marriage administration services at the KUA in Sukorambi District, while informants were selected using a purposive sampling technique consisting of the Head of KUA, Operational Service Administrator, First Expert Registrar, and SIMKAH user couples. The main research instrument was the researcher with data collection techniques through observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, drawing conclusions, and source triangulation to ensure data validity. The results of the study indicate that the implementation of SIMKAH improves productivity, service quality, time efficiency, access flexibility, user satisfaction, data security, and ease of administration management, although there are still obstacles such as low socialization and national server disruptions.The conclusion of the study states that online-based SIMKAH has been implemented effectively in marriage administration services at the KUA of Sukorambi District, however, optimization of socialization and system development is still needed to improve the quality of service